Factors Motivating The Local Community of Belawa, Wajo Regency, South Sulawesi Province to Engage in Edible Bird’s Nest Industry In The Perspective of Islamic Business Ethics - Agusdiwana Suarni; Asriati Asriati; Sulaiman Masnan; Fitriani Fitriani (Asosiasi Fakultas Ekonomi dan Bisnis Perguruan Tinggi Muhammadiyah, 2019)
This study aims to determine the factors that motivate the local community of Belawa sub-district, Wajo regency, South Sulawesi, to engage in edible bird’s nest industry. Edible-nest swiftlet farming becomes a rife among the agricultural community in the area, particularly after the issuance of MUI Fatwa No. 2 of 2012 concerning the lawful consumption of edible bird’s nest as well as the lawful swiftlet farming in Islam along with several requirements including the birds should not be tortured during the process. This study is a qualitative research in which qualitative analysis was performed to find out and learn directly about the actual situation and interaction between the community and the presence of swiftlet farming. The findings reveal that the factors motivating people to engage in edible bird’s industry are the prospective profits of the business, frequent agricultural crop failures, and the permit to consume bird’s nest based on Islamic law as well as the permit to farm the bird based on Islamic business ethics.